2005
DOI: 10.1016/s0002-9440(10)61208-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Interstitial Fibroblasts in an Accelerated Model of Angiotensin II-Induced Renal Fibrosis

Abstract: To determine whether previous renal injury accelerates the progression of glomerulosclerosis and interstitial fibrosis, we examined the effect of treating rats with angiotensin II after Habu venom injury. After initiating disease, we examined the origin of interstitial myofibroblasts by locating ␣-smooth muscle actin (␣-SMA)-positive and Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 49 publications
7
83
0
2
Order By: Relevance
“…However, it should be noted that activated resident interstitial fibroblasts may not be the only cells participating in extracellular matrix production. There have been reports that bone marrow-derived cells (39,40), transdifferentiated tubular epithelial and endothelial cells [via epithelial-to-mesenchymal (EMT) (39,41) and endothelial-tomesenchymal (EndMT) transition (4), respectively], and periadventitial cells (42,43) could also contribute to the population of interstitial matrix-producing cells in renal fibrotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that activated resident interstitial fibroblasts may not be the only cells participating in extracellular matrix production. There have been reports that bone marrow-derived cells (39,40), transdifferentiated tubular epithelial and endothelial cells [via epithelial-to-mesenchymal (EMT) (39,41) and endothelial-tomesenchymal (EndMT) transition (4), respectively], and periadventitial cells (42,43) could also contribute to the population of interstitial matrix-producing cells in renal fibrotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…11,24 Male C57BL/6 mice (6 weeks old) were injected via tail vein with 0.2 mg Texas Red-dextran (3000 MW, Invitrogen) in 0.2 ml PBS. UUO or sham-operation was performed 48 hours later, and kidneys were harvested 3 to 14 days after surgery.…”
Section: In Vivo Labeling Of Proximal Tubular Cells With Fluorescent mentioning
confidence: 99%
“…10 -12 In a rat model of angiotensin II-induced renal fibrosis, fibroblasts originate from encroachment of interstitial myofibroblasts from the perivascular space rather than via EMT. 11 To further evaluate the role of EMT in nephron loss in obstructive uropathy, we performed lineage analysis using genetically modified mice in which epithelial cells of the proximal and distal nephron were labeled and cell fate was followed.…”
mentioning
confidence: 99%
“…28 Although the role of myofibroblasts in renal fibrosis is widely accepted, their origin and fate are still debated. 19,29 Recently, it has been shown that kidney tubular epithelial cells acquire mesenchymal features in response to TGF-␤1, but they accompanied no de novo expression of ␣-SMA. 30 Thus, TGF-␤1 does not necessarily induce myofibroblast transdifferentiation in a certain cell types including the PCK cholangiocytes, and in these cell lines TGF-␤1 may act as an inducer initiating a cascade of dedifferentiating events.…”
Section: Sato Et Almentioning
confidence: 99%